ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN SINGLE INDEX MODEL DAN CAPM PADA JAKARTA ISLAMIC INDEX 70 (JII 70) - Putri Anastasya (2022)
This study uses a quantitative descriptive type with the aim of knowing the combination of stocks that are consistently listed on the Jakarta Islamic Index 70 (JII 70) in the period June 2018 - November 2020 as an optimal portfolio composition. Through the Single Index Model and CAPM, it is continued by measuring the portfolio performance of the results of the two methods as a comparison. The results of this research analysis are: (1) In the Single Index Model method, 13 forming stocks are obtained with an Expected Return portfolio of 0.0914 or 9.14% with a Portfolio Risk of 0.0393 or 3.93%. (2) The CAPM method produces 27 forming stocks accompanied by an Expected Return Portfolio of 0.0003 or 0.03% with a Portfolio Risk of 0.0373 or 3.73%. (3) Of the two methods that are more optimal in forming the Optimal portfolio, namely the Single Index Model with a risk of 3.93%, the amount is not too far from the CAPM with a risk of 3.73% but the SIM Return is greater, namely 9.14% and is proven by the measurement Portfolio performance with Treynor, Jensen and Sharpe, the Single Index Model value is greater than the CAPM even Jensen's CAPM reaches a value below 0, which is -0.01076.